Pengaruh Ankle Strategy Exercise terhadap Peningkatan Keseimbangan Statis pada Lansia Pasca Stroke - Achwan Achwan; Fitria Syifa Ainulhaya Wirawan; R Liza Laela Abida (Jurnal Sehat Mandiri, 2025)
Stroke is a common health issue among the elderly, primarily due to the aging process. Post-stroke changes in the elderly often include muscle weakness, decreased tissue flexibility, and sensorimotor control problems, which can lead to balance disorders. Ankle strategy exercise is a form of training that stimulates the musculoskeletal system, particularly in the lower extremities. This study aims to determine the effect of ankle strategy exercise intervention on static balance in elderly people after stroke. This research employed a pre-experimental design with a one-group pre-test and post-test approach. A total of 17 elderly participants were selected from PSTW Budi Mulia 4, East Jakarta, using purposive sampling based on predetermined criteria. The intervention was conducted three times per week over a period of four weeks. Static balance was measured using the Functional Reach Test. Result : The average static balance score before the intervention was 15.75 cm, which increased to 23.88 cm after the intervention. Bivariate analysis using the paired sample t-test revealed a significant difference with a p-value of 0.000 (p < 0.05). Conclusion : Ankle strategy exercise has a significant positive effect on improving static balance in elderly individuals after stroke.